Discourse Analysis of English Texts (Eurasian Scientific Herald, 2023)
The purpose of the work is to reveal the content and methods of cognitive-discursive analysis of English-language texts in the discourse of corporate social responsibility (CSR).The principles of discourse analysis (linguistic indexicality, from nativeness and authentication), a method of linguocognitive interpretation of CSR texts with elements of stylistic and sociocultural analysis.